Efficient selective deacetylation of complex oligosaccharides using the neutral organotin catalyst [tBu2SnOH(Cl)]2. (December 2020) - Ni, Minghong; Guerrini, Marco; Naggi, Annamaria; Petitou, Maurice
Abstract: Tetra- tert -butyl-3-chloro-1-hydroxydistannoxane has been found to selectively cleave with high efficiency primary acetates on complex oligosaccharides containing esterified l -iduronic acid and bearing an anomeric acetate. This tin based catalyst was found much more effective than magnesium methoxide to carry out selective deacetylation. Graphical abstract: Image 1 Highlights: Efficient selective deacetylation using organotin catalyst.